2020
DOI: 10.1089/vbz.2019.2576
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the Bloodmeals ofCulexspp. Mosquitoes at Natural Habitats in Singapore to Investigate the Potential Risk of Japanese Encephalitis Virus and West Nile Virus Transmission

Abstract: Japanese encephalitis virus (JEV) and West Nile virus (WNV) are arboviruses primarily transmitted by Culex spp. mosquitoes. Birds are the primary hosts for JEV and WNV. Recent WNV outbreaks in Europe and United States and their association with migratory birds highlight the importance of understanding the feeding host preference of potential vectors for outbreak preparedness, especially in nonendemic settings. Singapore is nonendemic to JEV and WNV, but is a stopover site for migratory birds of the East Asian-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…Here, we found that the principal vector for JEV fed on both mammalian and avian hosts or was in contact with more than one host during a single gonotrophic cycle, similar to the findings in villages in India (Arunachalam et al 2005) and natural bird habitats in Singapore (Yeo et al 2020). In line with this study, Cx .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Here, we found that the principal vector for JEV fed on both mammalian and avian hosts or was in contact with more than one host during a single gonotrophic cycle, similar to the findings in villages in India (Arunachalam et al 2005) and natural bird habitats in Singapore (Yeo et al 2020). In line with this study, Cx .…”
Section: Discussionsupporting
confidence: 82%
“…tritaeniorhynchus , Kamoike in Kaga City, showed true ornithophilic feeding patterns. Yeo et al (2020) similarly reported a blood-feeding preference for Cx . bitaeniorhynchus as “primarily ornithophilic,” albeit occasionally opportunistic feeders on humans.…”
Section: Discussionmentioning
confidence: 97%
“…Information and education on public to use bed-nets or insect-repellents as their personal protection measures along with implementation of a good sanitation may contribute to reduce contact with the mosquito vector. Similarly, housing the pigs indoor with anti-mosquito nets or screens especially during the peak of vector activity may minimize contact the mosquitoes to the animals [ 87 , 88 ]. Modification of rice paddy fields management for water and fertilizer usage and separating the paddy fields or preventing stagnant water around the pig farms are other strategies that may also limit contact between mosquitoes, pigs and humans.…”
Section: Resultsmentioning
confidence: 99%
“…Although JEV has only been detected in the rural forested areas of Singapore thus far, increasing urbanization and the push for ecological conservation [67,68] result in close interactions between human dwellings and the habitats that are favored by culicine vectors and JEV hosts. A survey of bloodmeals of Culex mosquitoes in Singapore showed that JEV vectors opportunistically feed on humans [69], while a study of changing JEV epidemiological characteristics in metropolitan areas showed an apparent correlation between the presence of herons and the number of JE cases in the absence of pig farming [70]. It is thus necessary to maintain entomological and virological surveillance to keep track of possible enzootic JEV variants, thereby allowing for more leeway in containing any vector-human transmission events.…”
Section: Discussionmentioning
confidence: 99%